PEMBELAJARAN POLA BILANGAN MELALUI PERMAINAN TRADISIONAL NASI GORENG KECAP - Rosikhoh, Dewi; Abdussakir, Abdussakir (Jurnal Tadris Matematika, 2020)
The development of games in the technological acceleration era nowadays endangers the extinction of traditional games. Therefore, the integration of Learning with Cultural Local Wisdom was needed to keep those cultures. The purpose of this research was to create an integrated learning design using number patterns material through the traditional game of Nasi Goreng Kecap. This research is a qualitative research with a design research approach and development studies type. The results showed that Nasi Goreng Kecap's traditional game had five steps in the process of the game. The second stage of this game contains the concept of number patterns. That's why, through this Nasi Goreng Kecap traditional game, it was able to be designed a process of learning that integrates mathematics with local wisdom culture. In those designed for integrative learning, students were arranged to be several groups with a maximum of each group was six students. Each group was played those games until the second stage only. Group worksheets had been provided by the teacher to direct the students in making patterns generalization from the second step of the Nasi Goreng Kecap traditional game.